ANALISIS INFRASTRUKTUR CLOUD DAN NETWORKING UNTUK SISTEM TELEMEDICINE BEBASIS CLOUD DI DAERAH TERPENCIL - shofiyyah_ti shofiyyah (Framework : Jurnal Ilmu Komputer dan Informatika, 2026)
ABSTRACT Limited access to healthcare services in remote areas remains a significant challenge due to long distances, shortages of medical personnel, and inadequate network infrastructure. Cloud-based telemedicine has emerged as a potential solution by utilizing cloud computing and networking technologies to provide accessible remote healthcare services. This study aims to design a cloud and networking infrastructure to support the implementation of cloud-based telemedicine systems in remote regions. The research employs a literature review approach by examining studies related to telemedicine, cloud computing, networking, the Internet of Things (IoT), and edge computing. The findings indicate that an architecture consisting of client, network, and cloud layers can effectively support remote healthcare services. The proposed infrastructure includes application servers, database servers, storage servers, load balancers, firewalls, and container technologies to enhance system scalability and efficiency. Security is strengthened through data encryption, user authentication, and role-based access control. Furthermore, load balancing, auto-scaling, caching, data compression, and Quality of Service (QoS) contribute to improved system performance under limited network conditions. The integration of IoT and edge computing also enables real-time patient monitoring and faster data processing. Overall, the proposed infrastructure demonstrates the potential to provide a secure, flexible, and scalable solution for improving healthcare accessibility in remote areas.